Improving the processability and mechanical strength of self-hardening robocasted hydroxyapatite scaffolds with silane coupling agents - Pańtak, Piotr; Czechowska, Joanna P.; Kashimbetova, Adelia; Čelko, Ladislav; Montufar, Edgar B.; Wójcik, Łukasz; Zima, Aneta (Journal of the mechanical behavior of biomedical materials, 2025)
Bone cements are the subject of intensive research, primarily due to their versatility and the increasing importance for personalized medicine. In this study, novel hybrid self-setting scaffolds, based on calcium phosphates and natural polymers, were fabricated using the robocasting technique. Additionally, the influence of two different silane coupling agents, tetraethyl orthosilicate (TEOS) and 3-glycidoxypropyltrimethoxysilane (GPTMS), on the physicochemical and biological properties of the obtained materials was thoroughly investigated. The chemical and phase compositions (XRF, XRD, FTIR), setting process, rheological properties, mechanical strength, microstructure (SEM), and chemical stability in vitro were comprehensively examined. The use of silane coupling agents improved compressive strength of the scaffolds from 5.20 to 9.26 MPa. The incorporation of citrus pectin into the liquid phase of the materials, along with the use of a hybrid hydroxyapatite-chitosan powder, not only facilitated the development of printable pastes suitable for robocasting but also enhanced the physicochemical properties of the robocasted scaffolds. The results presented in this study underscore the beneficial influence of silane coupling agents on the characteristics of calcium phosphate-based bone scaffolds. Developed robocasted scaffolds hold great potential for applications in the field of bone tissue engineering and personalized medicine. Further in vitro and in vivo studies are necessary to validate their suitability for clinical applications.